2015
DOI: 10.1007/s10152-015-0438-3
|View full text |Cite
|
Sign up to set email alerts
|

Interannual variations in the hatching pattern, larval growth and otolith size of a sand-dwelling fish from central Chile

Abstract: The interannual variation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Seawater hydrographic features were kept relatively similar during autumn and winter, as well as the estimated size-at-hatch and growth rates of larval A. crinitus . For cryptobenthic fish species, larval growth rates seem to vary at larger temporal scales, such as in stargazers (family Dactyloscopidae, Rodríguez-Valentino et al ., 2015; Castillo-Hidalgo et al ., 2018). The lack of seasonality in the early life history traits of A. crinitus may be linked to the environmental stability of the water column structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seawater hydrographic features were kept relatively similar during autumn and winter, as well as the estimated size-at-hatch and growth rates of larval A. crinitus . For cryptobenthic fish species, larval growth rates seem to vary at larger temporal scales, such as in stargazers (family Dactyloscopidae, Rodríguez-Valentino et al ., 2015; Castillo-Hidalgo et al ., 2018). The lack of seasonality in the early life history traits of A. crinitus may be linked to the environmental stability of the water column structure.…”
Section: Discussionmentioning
confidence: 99%
“…Growth rates estimated for larval A. crinitus were similar to those described for other cryptobenthic fish larvae (clingfishes, Contreras et al ., 2013; triplefin, Palacios-Fuentes et al ., 2014; sand stargazer, Rodríguez-Valentino et al ., 2015) and adults (e.g. gobiids Eviota spp., 0.20–0.25 mm day −1 , Depczynski & Bellwood, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that littoral species from the Humboldt Current Ecosystem (HCS) display lunar and semi‐lunar hatching events, particularly in fishes from families Tripterygiidae (threefin blennies), Gobiesocidae (clingfishes) and Dactyloscopidae (sand stargazers) (Contreras et al ., ; Palacios‐Fuentes et al ., ; Rodríguez‐Valentino et al ., ). Other species show a reduction of hatching events during the new moon, such as the labrisomid blenny Auchenionchus crinitus (Jenyns 1841) (Landaeta et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Other species show a reduction of hatching events during the new moon, such as the labrisomid blenny Auchenionchus crinitus (Jenyns 1841) (Landaeta et al ., ). However, the hatching pattern may vary at seasonal and inter‐annual scales (Castillo‐Hidalgo et al ., ; Rodríguez‐Valentino et al ., ). Taking into account these results, it is plausible that diet of early life stages of littoral fishes from HCS may be influenced by the lunar cycle.…”
Section: Introductionmentioning
confidence: 97%
“…For example, hake, Merluccius gayi Guichenot, 1848, change their spawning location, egg size and the vertical migration pattern of their larvae between the main (spring) and secondary (early autumn) reproductive seasons (Landaeta & Castro, 2012). Among ELT, hatching patterns, growth and survival have crucial importance in determining the recruitment level of year classes in fish populations (Watanabe et al ., 2014) and may vary at differing temporal and spatial scales (Plaza et al ., 2003; Rodríguez-Valentino et al ., 2015). Additionally, developmental instabilities (i.e.…”
Section: Introductionmentioning
confidence: 99%